Pengaruh Human Capital dan UMR terhadap Tingkat Pengangguran Terbuka di Sumatera Utara Tahun 2004-2021 - Margaretha, Dewi; Purba, Kristin Yenita; Karo-Karo, Laura Elfina; Mirnawati; Putri, Nova Khairunisa; Suharianto, Joko (Ikatan Da'i Indonesia, 2024)
This research aims to find out how much influence the Human Development Index (HDI), Regional Minimum Wage (UMR) has on the Open Unemployment Rate in North Sumatra in 2004-2021. This research uses secondary data obtained from the Central Statistics Agency (BPS). The technique used in this research is data analysis using the multiple regression method, the results show that the Human Development Index (HDI) has a positive effect on the unemployment rate in North Sumatra Province in 2004-2021. UMR has a positive effect on the unemployment rate in North Sumatra Province. Partially, the HDI variable has a positive and insignificant effect on unemployment in North Sumatra in 2004-2021 with a prob value of 0.0034>0.05. Partially, the UMR variable has a positive and significant effect on the unemployment rate in North Sumatra in 2004-2021 with a prob value of 0.0001